Causes and risk factors of neonatal mortality through the AMP-SR framework: a scoping review in Indonesia - Sulicha Nurhayati; Martha Irene Kartasurya; Cahya Tri Purnami (Intelektual Pustaka Media Utama, 2026)
Neonatal mortality in Indonesia continues to increase, especially during the first 0-6 days of life, indicating persistent gaps in the quality of maternal and neonatal care. The maternal perinatal surveillance and response audit (AMP-SR) is implemented to identify causes of death and guide preventive and curative actions. This scoping review aims to explore the causes and risk factors of neonatal mortality using the AMP-SR framework. Article searches were conducted in Google Scholar, Garuda, and PubMed using the keywords (“Neonatal Death” OR “Cause of Death” OR “Kematian Neonatal”) AND (“AMP-SR” OR “Death Notification”). Inclusion criteria comprised primary studies published in Indonesian or English between 2021 and 2025 that examined neonatal deaths using the AMP-SR approach. Seventeen articles were selected and thematically analyzed following the PRISMA guidelines. The main causes of neonatal death were clinical conditions, including asphyxia, prematurity, sepsis, hypothermia, and congenital abnormalities. Identified risk factors encompassed maternal age, pregnancy complications, referral delays, inadequate quality of care, and limited health worker competence. Most neonatal deaths occurred within the first 72 hours of life, predominantly among male infants with low birth weight or gestational age under 37 weeks. These findings demonstrate that neonatal mortality results from interconnected medical, maternal, and health system factors that can be systematically identified through AMP-SR. From a policy and practice perspective, strengthening the routine use of AMP-SR findings to inform targeted quality improvement, referral system strengthening, and workforce capacity-building is essential to reduce preventable neonatal deaths in Indonesia.